Formal verification and implementation of safety computer communication management mechanism - Liang LIANG; Yuan CAO; Lian-chuan MA; Yu-zhuo ZHANG; Heng-kui LI (Tongxin xuebao)
In order to improve the system compatibility of the safety computer of the next generation train operation con-trol system, first of all, the structure was analyzed and the management mechanism was designed, the state transition model of management unit was established, and the correctness of the model was verified by formal verification tools at the same time. Then the software and hardware which based on micro controller unit (MCU) were designed and imple-mented. The verification and test results show that the management mechanism design meets the design requirements, the management unit can achieve the expected state transfer function.